ACCOUNTING INFORMATION AND STOCK PRICE FLUCTUATIONS AMONG LISTED SERVICE FIRMS IN NIGERIA (Journal of Global Accounting, 2024)
This study was set to investigate the effect of accounting information on stock price fluctuations of listed service firms in Nigeria. The specific objectives of the study were; to examine the influence of Return on Assets(ROA), Operating cash flow(OCF), Earnings per share (EPS), on their stock prices measured by Average share price (ASP). The study adopted the ex post facto research design and the population comprised of twenty-two listed service firms in Nigeria. A sample size of seventeen firms were purposively selected from the service sector of the Nigerian Exchange Group (NGX), from 2010-2022. The data were obtained from annual reports of the firms included in the sample.  The data were analyzed using descriptive tools, correlational and regression analyses. The pooled ordinary least square regression technique was used in testing the hypotheses of the study. The results showed that: return on assets (ROA) has negative statistically significant effect on Market Share Price (MSP) of service firms listed on the Nigeria Exchange Group (p-value = 0.007); Operating Cash flow (OCF) has no significant effect on Market Share Price (MSP) of service firms in Nigeria (p-value = 0.131); while Earnings per share (EPS) has positive significant effect on Market Share Price (MSP) of service firms listed in Nigeria (p-value = 0.000). In conclusion, investors in Nigerian service sector may focus more on earnings and growth prospects rather than current cash flow when valuing stocks. The study recommends that Investors should not rely solely on ROA in their decisions. They should consider a broader range of metrics, including EPS and potentially industry-specific measures, when evaluating service companies. Also, the Financial Reporting Council of Nigeria should create and update accounting standards to better reflect the valuation of service firms in Nigeria, and implement measures to enhance transparency and investor access to cash flow information..
Keywords: Accounting Information; Average share price; Earnings per share; Operating cash flow; Return on Assets; Stock Price fluctuations